Relectura transcultural de un clásico revolucionario: Trágame tierra de Lizandro Chávez Alfaro - Rothe, Thomas (2018)
Although Lizandro Chávez Alfaro’s Trágame tierra (1969) is recognized as the first contemporary Nicaraguan novel, it remains marginal in the panorama of Latin American literary criticism. The few critical readings tend to emphasize its depiction of revolutionary efforts against the Somoza dictatorship, placing little importance on regional elements, particularly the culture of the so-called Atlantic Coast. This article analyzes the novel from a transcultural perspective, as outlined by Ángel Rama, in order to discuss how the cultural otherness of Nicaragua’s Caribbean coast creates friction in the national literary discourse. The paper focusses on different forms of representing the clash between State modernization and the Caribbean cultural difference through subaltern characters, the plurality of names, and tensions between orality and writing. These elements form the pieces of a transcultural narrative that stresses the inherent conflicts in cultural symbiosis.